Framing Violence and Serial Murder in My Friend Dahmer and Green River Killer. Issue 1 (23rd March 2017) - Earle, Harriet
Abstract : The comics form has not remained untouched by true crime's massive surge in status across popular culture, especially in America. Comics as a form is uniquely positioned to represent violent and graphic narratives in such a way as to maximise reader affect and create a chronicle of crime that is both entertaining and captivating, guiding and being guided by the reader. Two comics have received massive critical acclaim for their portrayals of 'famous' American serial killers: Jeffrey Dahmer in Derf's My Friend Dahmer (2012 ) and Arthur Shawcross in Jeff Jensen & Jonathan Case's Green River Killer (2011 ). This article considers the framing techniques deployed in both comics. I consider how these two comics, distinct in their artistic presentation and their focus, frame their respective subjects and represent the complexities of serial murder. To conclude, I perform a close analysis of one framing aspect of My Friend Dahmer and expand on what the execution of this technique can tell us about comics as a true crime form.